SPATIAL-TEMPORAL DYNAMICS OF THE SPREAD OF DENGUE HEMORRHAGIC FEVER USING EPIDEMIC FOREST - Yulita Trida Tahu, Maria
Dengue fever outbreaks are a major public health issue in the Philippines, occurring almost every year during specific seasons. While dengue fever is endemic throughout the country, only a few regions record higher case numbers or even initiate outbreaks significantly earlier than others. This evidence presents a challenge for researchers and policymakers in comprehending the spatiotemporal transmission of dengue fever. This study focuses on clinical data related to dengue fever in several provinces in the Philippines, including North Cotabato, South Cotabato, Sarangani, Sultan Kudarat, Agusan Del Norte, Agusan Del Sur, Dinagat Islands, Surigao Del Norte, and Surigao Del Sur. From these nine provinces, we conduct city-level analyses, revealing that cities with higher case counts tend to experience outbreaks earlier and have the potential to transmit the disease to other areas. Furthermore, we construct an epidemic forest to estimate the spatial patterns of dengue fever spread during each outbreak period, allowing us to infer which areas are infecting other areas. In each outbreak period, the models consistently show that highland areas dominated by forests are the primary sources of endemic cases. One possible explanation for this finding is that forests, in general, provide a climate conducive to mosquito survival.